Sports event management the Caribbean experience - Jordan, Leslie-Ann (New directions in tourism analysis, 2011)
The CWC 2007 was the first time in any sport, a World Cup was staged in nine independent countries. Exploring sports event management from a Caribbean, small island developing state perspective, this volume uses the events of the recently held Cricket World Cup 2007 (CWC 2007) as a launching pad for identifying best practices and the way forward.